Environmental beliefs and marine pro-environmental behaviors: mediating roles of responsibility and values among Chinese university students - Zhang, Li; Yang, Lili; Zhou, Jiquan; Wang, Linzhao (Frontiers in Psychology, 2025)
IntroductionThis study investigates the psychological mechanisms through which general environmental beliefs influence marine pro-environmental behaviors among Chinese university students, focusing on the parallel mediating roles of marine environmental responsibility and marine environmental value orientations.MethodsA crosssectional survey was conducted with 1,206 students from 23 universities across 11 provinces in China, using standardized instruments adapted from validated environmental psychology scales. Correlation analysis, hierarchical regression, and parallel mediation modeling with the PROCESS macro (Model 4) were employed to test the hypothesized independent mediation pathways.ResultsGeneral environmental beliefs significantly predicted pro-environmental behaviors both directly and indirectly. Responsibility and value orientations functioned as two independent and equally strong mediators, highlighting parallel psychological pathways. Neither gender nor age exerted significant effects, underscoring the predominance of psychological over demographic determinants.DiscussionGrounded in the Value–Belief–Norm theory and conceptually supported by the Theory of Planned Behavior and the Norm Activation Model, this study provides an integrated framework explaining how cognitive awareness translates into marine conservation behavior. The findings underscore the dual importance of normative obligation and value-based motivation in promoting youth engagement in ocean protection and suggest that marine education and policy design should incorporate strategies that strengthen both responsibility and value orientations.